PERFIL EPIDEMIOLÓGICO DO CÂNCER DE MAMA, OVÁRIO E COLO DO ÚTERO EM MULHERES JOVENS DE 2017 A 2018 (REMUNOM, 2025)
Purpose: To draw an epidemiological profile of breast, ovarian and cervical cancer in young women from 2017 to 2018. Methodology: The epidemiological study to be carried out is cross-sectional, exploratory and descriptive, where data analysis was carried out of breast, ovarian and cervical cancer in young women reported in the state of Pernambuco, during the years 2017 to 2018. Risk factors were observed, such as age, heredity, in addition to the social conditions of these patients, such as level of education and skin color/race. Results: By carrying out the research, it was possible to provide the institution with an epidemiological and sociodemographic profile of young women diagnosed with the types of cancer studied, in order to relate the cancers with the identified risk factors, and contribute with scientific evidence for studies and future research on this topic. Conclusion: The research sought to stimulate the expansion of data beyond the hospital cancer registry, providing crucial information for the prevention and control of the cancers studied, especially in young women.